Avaliação de diferentes processos de aproveitamento de águas residuais e lodo de esgoto dentro de uma visão bioeconômica - Duarte, Kaique Guedes [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Adverse environmental conditions, such as climate change and large emissions of pollutants in the atmosphere, together with a new economic initiative in sustainability, bring a need to react with investment and research on the world's energy consumption policy, with the encouragement of alternative energies. For these reasons, renewable energies have been highly developed in the energy matrix in recent years, demonstrating their importance in Brazil and in the world. Another worrying environmental issue is the poor utilization and distribution of urban sewage in Brazil, since much of the sewage collected is returned to the environment without treatment. The production of biomass derived from sewage treatment is an alternative that incorporates the sustainable use and exploitation of a source of energy little used. The present work aims to address the conceptual and technical aspects related to the recovery and energetic use of the derivatives of sanitary sewage treatment, analyzing existing implementations and possible innovative alternatives to verify the feasibility for future projects in Sewage Treatment Stations in the country and in the world

As condições adversas ambientais, como alterações climáticas e aumento nas emissões de poluentes na atmosfera, juntamente com iniciativa econômica em sustentabilidade, motivou a necessidade de reagir com investimento e pesquisa sobre a política de consumo de energia no mundo, com o incentivo às energias alternativas. Diante desse cenário, as energias renováveis passaram a ter alto potencial de uso dentro da matriz energética nos últimos anos, demonstrando sua importância no Brasil e no mundo. Uma questão ambiental global de destaque é o mau aproveitamento e distribuição do esgoto urbano, uma vez que grande parte do esgoto captado retorna ao meio ambiente sem tratamento. A produção de biomassa derivada do tratamento de esgoto é uma alternativa que incorpora o uso sustentável e a exploração de uma fonte de energia pouco aproveitada. O presente trabalho tem por finalidade abordar os aspectos conceituais e técnicos relacionados à recuperação e uso energético dos derivados do tratamento do esgoto sanitário, analisando implementações já existentes e possíveis alternativas inovadoras para verificar a viabilidade para futuros projetos em Estações de Tratamento de Esgoto - ETE no país e no mundo
Evaluation of different wastewater and sewage sludge processes from a bioeconomic perspective
Keywords: Energia - Fontes alternativas; Aguas residuais; Biomassa; Esgotos; Sustentabilidade; Renewable energy sources